Manajemen Sarana dan Prasarana dalam Meningkatkan Kreativitas Peserta Didik di MA NW Bungtiang - Baiq Irani Diah Utami; Sulistianing; Abdul Haris Rasyidi (Al-Gafari : Manajemen dan Pendidikan, 2024)
Facilities and infrastructure management in schools must be done well with good planning. Current educational facilities and infrastructure play an important role in supporting the smooth running of the educational process. Even though teaching and learning activities are good, if they are not endorsed by supporting educational facilities and infrastructure, the results achieved will not be optimal. This research aims to determine the management of educational facilities and infrastructure in schools to increase learning creativity. By formulating the problem of how to manage the management of facilities and infrastructure in increasing student creativity at MA NW Bungtiang, what are the supporting and inhibiting factors for managing facilities and infrastructure in increasing student creativity? This research uses a qualitative descriptive approach, the subjects of this research are the school principal, deputy head of facilities, and students. The methods used in collecting data in this research were observation, interviews, and documentation. The validity of the data by triangulating sources and methods is then analyzed using an interactive model consisting of data collection, data reduction, data presentation, and concluding. The results of this research can be concluded that the educational facilities and infrastructure at MA NW Bungtiang can be managed and the management of the facilities and infrastructure runs smoothly.